2011
DOI: 10.1074/jbc.c111.265934
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion Receptor GPR133 Couples to Gs Protein

Abstract: Adhesion G protein-coupled receptors (GPCR), with their very large and complex N termini, are thought to participate in cell-cell and cell-matrix interactions and appear to be highly relevant in several developmental processes. Their intracellular signaling is still poorly understood. Here we demonstrate that GPR133, a member of the adhesion GPCR subfamily, activates the G s protein/adenylyl cyclase pathway. The presence of the N terminus and the cleavage at the GPCR proteolysis site are not required for G pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 49 publications
7
97
0
1
Order By: Relevance
“…Interestingly, adhesion GPCRs frequently signal through Ga proteins. GPR56 has been reported to couple to Ga12/13 and Gaq/11 (25,27), GPR133 couples to Gas, and CD97 couples to Ga12/13 (28,47). Our study supports the idea that adhesion GPCRs also activate the classical receptor/G-protein signaling pathway.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, adhesion GPCRs frequently signal through Ga proteins. GPR56 has been reported to couple to Ga12/13 and Gaq/11 (25,27), GPR133 couples to Gas, and CD97 couples to Ga12/13 (28,47). Our study supports the idea that adhesion GPCRs also activate the classical receptor/G-protein signaling pathway.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, GPR56 has been shown via coimmunoprecipitation to interact with G␣ q/11 (Little et al, 2004), which is consistent with work on other receptor types demonstrating that receptors coupling to G␣ 12/13 can also typically couple to G␣ q/11 (Takashima et al, 2008). In a similar vein, overexpression of GPR133 in various cell types has been shown to stimulate G␣ s and promote cAMP generation (Bohnekamp and Schöneberg, 2011;Gupte et al, 2012). Gpr126 has also been shown to exert actions on Schwann cells consistent with a cAMP-and G␣ s -dependent mechanism (Monk et al, 2009), and GPR114 has been shown to constitutively increase cAMP levels when overexpressed in HEK293 cells (Gupte et al, 2012).…”
Section: Adhesion Gpcr Signaling Through G Proteinssupporting
confidence: 66%
“…Without a known ligand, overexpression of an adhesion GPCR or its ␤-subunit constitutively activates specific signaling pathways that are normally stimulated by agonist activation (13,24,25). The constitutive activities of orphan receptors have been used to characterize their downstream signaling activities (26,27).…”
Section: Vlgr1 Can Be Processed Into Two Fragments Aftermentioning
confidence: 99%